ANALISIS PENILAIAN MATERIALITAS LAPORAN KEBERLANJUTAN PADA 15 PERUSAHAAN MULTIFINANCE - Cindy Feliyanti (Jurnal Akuntansi, 2022)
The background is materiality which is emphazised in the report guidelines in order to improve the quality of sustainability reports. Related to the company’s social, economic, and environmental issues. The lack of research discussing the materiality analysis of sustainability repoerts, prompted the authors to raise issue about the definition of materiality, stakeholder engagement, and identification of key materiality issues. This study aims to determine the practice of materiality assessment in sustainability reports in current financing services. Using stakeholder theory, legitimacy theory, and sustainability reporting standards. Taking 12 qualitative studies on materiality and non-materiality, and 7 quantitative studies on CSR. This research method is qualitative with a research design that examines the materiality aspect of sustainability reports reported by 15 companies in the financing services sub-sector. 4 companies provided an explanation of how materiality was defined, while the other companies only developed their own approach without GRI guidelines. And only 2 companies provided detailed information of stakeholder engagement. And 3 companies that convey the main materiality problems indicated. Therefore, there is still a lack of uniformity in sustainability reports related to materiality assessment, lack of completeness and transparency in Indonesia, especially for companies in the financing services sub-sector.